EVALUATION OF GENERAL BUREAUCRATIC REFORM POLICIES WITHIN THE KUTAI KARTANEGARA REGENCY GOVERNMENT - Rahma Handaya; Kus Indarto; Cathas Teguh Prakoso (SOSIOEDUKASI, 2026)
This study aims to evaluate the implementation of General Bureaucratic Reform in the Kutai Kartanegara Regency Government using William N. Dunn’s evaluation framework. Bureaucratic reform is a national strategic agenda within the 2010–2025 Grand Design to build a clean, accountable, capable and service-oriented bureaucracy. Data were collected through interviews, observations and a review of official documents from the Ministry of State Apparatus and Bureaucratic Reform (KemenPANRB), and were subsequently analysed using a descriptive qualitative approach based on Dunn’s six evaluation criteria: effectiveness, efficiency, adequacy, fairness, responsiveness and accuracy. The main novelty of this evaluation of the General Bureaucratic Reform (RB) policy in the Kutai Kartanegara Regency Government (Kukar Regency Government) lies in the shift in focus from upstream administrative assessment towards agile, high-integrity performance-based governance (SAKIP) to support the ‘Golden Indonesia 2045’ vision. The research findings indicate positive achievements in the simplification of organisational structure (score of 100.45 per cent), yet weaknesses remain, such as in the development of the Integrity Zone (0.5), SPI (67.14 per cent) and SAKIP (65.93 per cent). Effectiveness remains partial, efficiency is low due to weak digital integration, adequacy and equity are insufficient, bureaucratic responsiveness is limited, and the relevance of policies does not yet fully align with local needs. This study offers practical contributions in the form of strategic recommendations for improvement, whilst also expanding the application of the Dunn framework at the regional level.